Sr, Nd and Pb isotope characterisation of the sources and sinks of terrigenous material in the North American Southwest and California Borderland Basins - Jardine, Gabriella; Crocker, Anya J; Bailey, Ian; Cooper, Mathew; Milton, James; Wilson, Paul A (In: Jardine, G et al. (2021): Sr, Nd and Pb isotope characterisation of the sources and sinks of terrigenous material in the North American Southwest and California Borderland Basins [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.932944, 2021)
Strontium, neodymium and lead isotopic signatures were measured on fluvially-derived and hemipelagic sedimentary horizons in Late Quaternary age marine sediments from Ocean Drilling Project sites 893 and 1015 in the California Borderland Basins. All samples had carbonates, organic material, biogenic silica and Fe-Mn oxides removed before full chemical digestion prior to analysis. Age estimates of samples based upon Rack and Merrill (1995), Roark et al. (2003), Romans et al. (2009), Balestra et al. (2018) and Du et al. (2018).
Keywords: dust; lead; Neodymium; North America; paleoclimatology; Quaternary; Radiogenic isotopes; Strontium (Sr)